Moisture requirements for successful development of Haemonchus contortus and Trichostrongylus colubriformis to third stage infective larvae - Khadijah Saad (Pulau Pinang: Universiti Sains Malaysia, 2014)
The overarching aim of the experiments conducted as part of this thesis was to determine the influence of moisture in the form of rainfall events (amount, timing and distriubution) and soil moisture (SM) on faecal moisture (FM) and development of H. contortus and T. colubriformis to infectice third stage larvae (L3).